Figuras Literarias: Imagen, metáfora, símil - Villafuerte Cuisano, Domingo (2018)
The theme of literary figures (they are unconventional ways of using words, accompanied by some phonic, grammatical or semantic particularities, which take them away from that habitual use) was developed with the students of third grade of secondary education, as a technique so that the written expression has coherence, order and harmony. Its use is sometimes unconscious and at other times with the intention of improving the sending of messages. Students use literary figures to give beauty and originality to their writings, giving greater force to their message. To generate their creativity in their creations use the main figures such as: Image, metaphor, simile, epithet, hyperbaton.